Karakterisasi dan Uji Kemurnian Klobazam secara Kromatografi Cair Kinerja Tinggi Sebagai Baku Pembanding Farmakope Indonesia - Endah Kristiana; Widya Sagita Br. Tampubolon; Atiek Supardiati E. S (Badan Pengawas Obat dan Makanan, 2022)
Clobazam is a drug with the chemical name 7‐chloro‐1‐methyl‐5‐phenyl‐1,5‐benzodiazepine, which is used to treat various types of epilepsy. Clobazam works on the brain and central nervous system to provide a calming effect. To maximize the therapeutic effect and reduce the drug's toxic effect, it is necessary to test to determine the levels in the sample of clobazam that fulfilled requirements. One way to control drugs is to strengthen the capacity and capability of testing by developing reference standards. The more reference standards developed, the more drug samples can be tested. The development of reference standards is aimed at producing the “Baku Pembanding Farmakope Indonesia (BPFI)” which can be used for qualitative and quantitative testing of clobazam samples. This test aims to produce the clobazam “Baku Pembanding Farmakope Indonesia (BPFI)” which fulfilled the characterization and purity requirements as a reference standard. Characterization was achieved by infrared spectroscopy with the wave number results showed aromatic C=C functional groups (1490.97 cm-1), C=O cyclic ketones (1670.35 and 1691.57 cm-1), and C-N amines (1330.88 and 1375.25 cm-1), UV-Vis spectroscopy results showed a wavelength of 230.5 nm, gas chromatography-mass spectroscopy results showed the main ion (m/z) of clobazam was 207 (C13H4NO2); 255.1 (C15H11ClN2); 257.1 (C14H9ClN2O); 258.1 (C14H10ClN2O); and 300 (C15H7ClN2O2), and 1HNMR, 13CNMR, HMQC, and HMBC spectroscopy which showed that the raw material was clobazam. The purity of clobazam was measured using HPLC-DAD and obtained a purity index of 1.0000 and a purity of 99.73% (n=20, SD= 0.01%, RSD=0.01%), and by DSC obtained a purity of 99, 33% and a melting point of 180.55oC. All validation parameters of the HPLC analysis method were specificity/selectivity, system-appropriate test (RSD = 0.05%), linearity (R = 0.9997) with a range of 0.015% to 0.045%, accuracy 0.19%, and precision 0, 01% have fulfilled the requirements. The characterization results of clobazam and determination of purity value ​​can be used as “Baku Pembanding Farmakope Indonesia (BPFI)” and used in qualitative and quantitative tests by all Indonesia FDA provincial offices and stakeholder ABG (Academic, Business, government).